Identification of anticholinergic activity of drugs of the Brazilian National List of Essential Drugs - Mariana S. LIMA; Adriano M. REIS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objectives: Identify drugs from the National List of Essential Medicines-Rename 2018 that have anticholinergic activity and scales of anticholinergic activity available for use in clinical practice. Methods: Drug utilization study, emphasizing the analysis of supply. The drugs included in Brazilian National List of Essential Drugs (BNLED) 2018 were classified according to level 3 of the chemical therapeutic anatomical classification. A literature review was performed to identify anticholinergic activity measurement scales. Anticholinergic activity of BNLED 2018 drugs was determined using the Composite anticholinergic scale. Results: It was identified two systematic reviews, among the 13 identified scales, Duran's Scale and Composite Anticholinergic Scale. Composite Anticholinergic Scale is the most comprehensive with 197 drugs. It was found that 14.6% of the drugs have anticholinergic activity and 69.1% are included in the basic component of the national list. Drugs with central nervous system activity constitute about 50% of the substances with anticholinergic activity, mainly comprised of antipsychotics, followed by cardiovascular system drugs, mostly represented by betablockers. The cumulative effect of anticholinergic activities, from several drugs prescribed concomitantly, reflects the importance of verifying prescriptions and aware health professionals of strategies to reduce this impact. Conclusions: To measure anticholinergic load in clinical practice, 13 scales are available. The most comprehensive scale is the Composite Anticholinergic Scale. Although medicines with anticholinergic activity are uncommon among medicines included in BNLED 2018, it is needed to provide information to prescribers due to the negative clinical outcomes attributed to cumulative anticholinergic burden.